1988
DOI: 10.1152/ajpgi.1988.254.3.g416
|View full text |Cite
|
Sign up to set email alerts
|

Functional coupling of tight junctions and microfilaments in T84 monolayers

Abstract: The actin-binding agent cytochalasin D (CD) in intact intestinal epithelium appears to elicit segmentation and contraction of a perijunctional ring of actomyosin and, consequently, to diminish tight junction resistance. We determined if an intestinal epithelial model composed of T84 cells also displayed such a perijunctional cytoskeletal specialization and, if so, whether exposure to CD also affected the tight junction barrier. We find T84 cells display a prominent perijunctional microfilament ring that is act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 0 publications
7
95
1
Order By: Relevance
“…Previous studies have shown that cytochalasins and Na ϩ -glucose co-transporter induced increase in intestinal TJ permeability in vitro and in vivo was triggered by MLCK-induced increase in MLC phosphorylation (42,56,57). MLC phosphorylation then leads to an energy-dependent contraction of peri-junctional acto-myosin filaments, and mechanical tension induced retraction of junctional membrane and TJ proteins, and functional opening of the TJ barrier (40,57,60). The over-expression of constitutively active MLCK has also been shown to cause MLC phosphorylation and functional opening of the TJ barrier in MDCK cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cytochalasins and Na ϩ -glucose co-transporter induced increase in intestinal TJ permeability in vitro and in vivo was triggered by MLCK-induced increase in MLC phosphorylation (42,56,57). MLC phosphorylation then leads to an energy-dependent contraction of peri-junctional acto-myosin filaments, and mechanical tension induced retraction of junctional membrane and TJ proteins, and functional opening of the TJ barrier (40,57,60). The over-expression of constitutively active MLCK has also been shown to cause MLC phosphorylation and functional opening of the TJ barrier in MDCK cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…, where is the ratio of permeability of the monolayer to Na ϩ over the permeability to Cl Ϫ ( ϭ P Na / P Cl ), ⑀ is the dilution factor (⑀ ϭ C basal / C apical ), and v ϭ eV / kT (where V is the dilution potential, k is the Boltzmann constant, e is the elementary charge, and T is the Kelvin temperature) (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Cells with a number of passages ranging from 12 to 21 were grown for 12-20 days on Transwell or Snapwell membrane filters led to the establishment of TER values ranging from 1250 to 5000 ⍀.cm 2 . Such resistance variation is attributable to monolayer to monolayer variation in tight junction permeability (37).…”
Section: Transepithelial Resistance Measurementsmentioning
confidence: 99%